The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ejh.12810
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B10 cells display an altered homoeostasis in acute graft‐versus‐host disease

Abstract: This is the first report demonstrating B10 cells in stem cell transplant recipients in the early post-alloSCT (30 d) period. Our data suggest a possible role for B10 cells in the pathophysiology of acute GvHD. Further longitudinal studies are warranted to understand the implications of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…They also reported a protective role for cord blood-derived Bregs against GVHD development in cord blood recipients. The role of Bregs in acute GVHD was further elucidated by Chakupurakal et al 35 In agreement with these studies, we found that a high dose of Bregs decreased the incidence of grades II-IV acute GVHD but had no negative effects on relapse after unmanipulated allografts (Table 2 and Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
“…They also reported a protective role for cord blood-derived Bregs against GVHD development in cord blood recipients. The role of Bregs in acute GVHD was further elucidated by Chakupurakal et al 35 In agreement with these studies, we found that a high dose of Bregs decreased the incidence of grades II-IV acute GVHD but had no negative effects on relapse after unmanipulated allografts (Table 2 and Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
“…Bregs have significant immunosuppressive abilities both in vitro and in vivo. Bregs prevent the onset of GVHD by inhibiting the differentiation of Th1 and Th17 cells and promoting the expansion of Tregs [ 29 , 41 , 42 ]. Therefore, MDSC-mediated expansion of Bregs is important for the treatment of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Bregs have signi cant immunosuppressive abilities both in vitro and in vivo. Bregs prevent the onset of GVHD by inhibiting the differentiation of Th1 and Th17 cells and promoting the expansion of Tregs [29,41,42]. Therefore, MDSC-mediated expansion of Bregs is important for the treatment of aGVHD.…”
Section: Discussionmentioning
confidence: 99%